The Impact of Digital Banking on Millennials' Financial Decision Making - Rozaki, Deki; Sarjono, John; Raharjo, Susilo Toto; Perdhana, Mirwan Surya (Research Horizon, 2025)
This study examines the impact of digital banking on the financial decision-making processes of millennials, addressing key challenges and opportunities. Through a mixed-methods approach, including surveys and interviews, we explore how accessibility, financial literacy, and behavioural patterns are shaped by digital banking tools. Our findings reveal that digital banking significantly enhances financial engagement among millennials, leading to more informed decisions and improved financial literacy through integrated educational resources. However, it also highlights a tendency toward impulsive spending and a lack of understanding of complex financial products. These dual influences underscore the need for financial institutions to develop user-friendly platforms that promote responsible financial behaviours. This research contributes to the understanding of how digital banking can be leveraged to support effective financial decision-making in a tech-savvy generation.